Pilgrimage, Politics and Surveillance : The temple of Jagannath and the colonial state in early 19th century Orissa - Ghosh, Ujaan (The international journal of religious tourism and pilgrimage, 2016)
The temple of Jagannath became central to colonial politics as early as the first year of British rule in Puri. Throughout the 19th century, the temple was an essential concern for British administrators, both in the colony as well as in the metropolis. In this paper, I demonstrate how pilgrimage became a pivotal anchor surrounding which a convoluted narrative of colonial politics played out. I have looked closely at the concept of itinerancy' associated with pilgrimage, and have tried to explain how itinerancy in the early 19th century became a governmental hazard for the colonial overlords. The constant fear of a faceless and mobile crowd prompted the advent of newer governmental techniques, primary of which was the documentation of pilgrim identities. My central concern is with the various modalities through which the government sought to bring pilgrims and pilgrimage under surveillance. The paper interrogates how in early 19th century Orissa, the innocuous act of pilgrimage was transformed into a deep political concern for the colonial state. In framing my narrative about the interaction between the temple and the colonial state, I have juxtaposed temple correspondence with the papers of the Board of Revenue and the House of Commons Parliamentary papers. I then look closely at the pilgrim networks of Puri and governmental concerns surrounding them. Such a study, I believe, will contribute to our understanding of Company rule in Orissa and the governance of a nascent colonial order.